How important are remittances to savings? Evidence from the Latin America and the Caribbean countries - John Bosco Nnyanzi; Nicholas Kilimani; John Bosco Oryema (IZA Journal of Development and Migration, 2022)
This paper investigates the direct and the indirect roles of migrant transfers in the saving behaviors of the Latin America and Caribbean (LAC) countries during the period 1997-2018. Using the autoregressive distributed lag (ARDL) panel estimation technique, the results based on the Pooled Mean Group approach provide strong evidence of the importance of inward remittances to savings. On average, an increase in inward remittances by 1% leads to about 0.10% increase in savings ceteris paribus, but the effect is quantitatively larger in the short-run than in the long-run, albeit more significant in the latter case. Quite outstanding here is the observation of the detrimental role of remittances on savings in the long-run once governance quality in aggregate and disaggregated forms are controlled for, suggesting possible adverse effects of remittances for economic development in the long-run. Nevertheless, macroeconomic stability as well as institutional quality, foreign direct investment (FDI), and foreign aid were found to be important moderators of the remittances-savings linkage. For the latter two variables, emphasis is on complementarity rather than substitutability between remittances, aid, and FDI. While in the short-run remittances appear to perform better in enhancing savings in countries where an improvement in corruption control is visible, political rights and civil liberties compliment migrant transfers in propelling savings in the long- and short-runs, respectively. Moreover, remittances are found to play a major role in ameliorating the adverse effects of the financial crisis on savings, just as they are observed to function as a lifeline to savings in countries with increasing macroeconomic instability in form of inflation, in the long-run. The findings are robust to the use of alternative estimation techniques. Policy recommendations are suggested.
Keywords: E21; O11; O16; F21; F22; 330; remittances; savings; finance; institutions; LAC